Acute Reversal of Vision Metamorphopsia: Report of Two Cases - Gondim, Francisco de Assis Aquino; de Araújo, Davi Farias; Sales, Paulo Marcelo Gondim (Journal of Health & Biological Sciences, 2014)
Purpose: Acute reversal of vision metamorphopsia (RVM) is a rare, paroxysmal, sudden and transient vertical inversion of vision, also known as floor-on-the-ceiling phenomenon. Its pathogenesis is uncertain, but it may due to transient impairment of vestibular projections to the parietal lobes. Case description: Here we present a case of a 60 year-old man with a right paramedian pontine stroke developed episodes of upside-down reversal of vision during transition from awake to sleep time (hypnagogic acute reversal of vision metamorphopsia) that subsided after treatment with gabapentin.